Analysis of the Influence of Social Media Use, Educational Technology, and Digital Identity on Educational Culture Change in West Java - Loso Judijanto; Bhaswarendra Guntur Hendratri; Sabil Mokodenseho; Tania Prinita Aulia Mamonto; Annisa Mokoginta (Westscience Press, 2024)
This study explores the impact of digital identity development, social media use, and educational technology integration on changes in educational culture in West Java, Indonesia. A quantitative strategy was used, collecting data from 120 teachers and students from different educational institutions through survey methodologies. The data was analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings show a strong correlation between the usage of social media, the integration of technology in education, the development of digital identities, and the transformation of educational culture. The results show that social media use, while to a lower degree, also plays a significant part in the shift in educational culture, but that digital identity and instructional technology have the most effects. For educators, policymakers, and academics looking to use digital technology to promote inclusive learning environments and positive educational reforms in West Java, these discoveries have important implications.